Bibliometric Analysis of Entrepreneurial Competencies in the Last 10 Years (2013-2023) - Hanifah, Ajeng Putri; Purnomo, Margo; Dai, Ratna Meisa (Fakultas Ekonomi Universitas Samudra, 2024)
This research uses bibliometric analysis to reveal state-of-the-art entrepreneurial competencies in the context of entrepreneurship. The method used in this research is quantitative research with the use of Scopus database assistance as well as VosViewer as an analysis tool. The limitation specified in this research is scientific publications published from 2013 to 2023. Countries with the highest productivity three largest rankings contributing to the theme of entrepreneurial competencies research are Malaysia, the United States, and India. The results of the bibliometric analysis reveal co-citation, bibliographical coupling, authors' keywords, and co-occurrence of all keywords. Further research in the future is expected to be able to investigate entrepreneurial competencies with novelty.